B981b Biologia de nidificação de Podium angustifrons KOHL, 1902 (HYMENOPTERA, Sphecidae) - Buss, Carlos Eduardo (2010)
Podium angustifrons is a species of solitary wasp which nests in pre-existing cavities, with neotropical distribution in French Guyana, Bolivia and Brazil. The aim of this study was to investigate the nesting biology of Podium angustifrons, discussing aspects of their life history. To capture the nests of P. angustifrons, wooden trap-nests were installed in the Parque Municipal das Araucárias, Guarapuava (PR), Brazil, from January 2003 to April 2009. A total of 29 nests were collected, all during the warmer months. These showed no vestibular and intercalary cells, and their closures were made up of chewed plants and mud mixed with organic materials and resin-coated surfaces, sometimes showing a layer of lichens. The cells were provisioned with various wild species of cockroaches (Chorisoneura sp, Riata sp and Helgaia sp) in the nymph stage and / or adults. The sex ratio was 4.6 females per male, significantly higher that the expected 1:1. Most pre-pupae entered diapause in winter with development time ranging from 187 to 283 days for females and 180 to 283 days for males. Deaths occurred in 41.66% of cells provisioned, 33.33% were attributed to faulty development and 8.33% to Chrysididae.